THE RELATIONSHIP BETWEEN PERSONALITY TYPE, FAMILY SUPPORT AND DEPRESSION IN INDONESIAN ELDERLY IN THE HOME CARE CENTER OF TRESNA WERDHA MINAULA, KENDARI, INDONESIA - Taamu, Taamu; Nurjannah, Nurjannah; Bau, Abd Syukur; Banudi, La (Public Health of Indonesia, 2017)
Background: Depression in elderly is widespread, often undiagnosed, and usually untreated.Objective: This study aimed to determine the relationship between personality, family support, and depression in elderly in the Home Care Center of Tresna Wedha Minaula Kendari.Methods: This was a correlational cross-sectional study conducted in 2015. The population in this study is all elderly people in the Home Care Center of Tresna Wedha Minaula Kendari as many as 90 persons. Of the total population, 41 samples were selected using purposive sampling. Data data were analyzed using frequency distribution and chi square test. Results: There were significant associations between personality type (p = 0.019), family support (p = 0.047), and depression in elderly persons. Conclusion: There is a significant relationship between personality type, family support, and depression in the elderly in the Home Care Center of Tresna Wedha Minaula Kendari. It is important to understand how the roles of personalities and family support from each family member contributes to depression.